Activity of glutaraldehyde at low concentrations against capsid proteins of poliovirus type 1 and echovirus type 25. - Chambon, M (1992)
The activity of glutaraldehyde (GTA) against capsid proteins of poliovirus type 1 and echovirus type 25 was studied to understand the mode of action of this reagent against enteroviruses. The viruses were treated with GTA concentrations ranging from 0.005 to 0.10%. In the poliovirus particles, high-molecular-weight products were formed by 0.05% GTA, whereas in the echovirus particles, they were formed at 0.005% GTA. These products consist of complexes composed essentially of VP1 and VP3. There seemed to be differences in the composition of the complexes in the two viruses. Cross-linkings between the two polypeptides of the poliovirus capsid may be due to the accessibility to GTA of lysine residues on the loops of VP1 and VP3, which twist out from the surface of the shell.